MODIFICATION OF TRADITIONAL FOOD (KLEPON CHEESECAKE) - Sukriadi, Erie Hidayat; Canty Zenitha (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2025)
Klepon is a traditional snack loved by people of all ages due to its dominant sweet, savory taste and soft texture. In an effort to preserve and develop traditional culinary delights, this research aims to assess consumer acceptance of modified Klepon Cheesecake by evaluating its quality in terms of taste, aroma, texture, and appearance. The product development was achieved by modifying the traditional klepon, made from glutinous rice flour, into a cheesecake with added kinca (palm sugar syrup) filling. This experimental research used qualitative methods and a descriptive approach, with data collected through organoleptic tests, observation, and literature review. The results showed that the modification was well-received by the panelists, who rated the texture and appearance highly. However, some panelists suggested enhancing the pandan flavor and coconut aroma to achieve a more balanced taste profile. Keywords: Food Modification, Traditional Food, Klepon, Cheesecake